Tinjauan Yuridis Terhadap Pelaksanaan Hak Kekayaan Intelektual Sebagai Upaya Memajukan Industri UMKM Di Kabupaten Semarang - Iftitah Dwi Aprilyani; Indra Yuliawan (ADIL Indonesia Journal, 2023)
Intellectual Property as defined in Law Number 7 of 1994 concerning ratification of the WTO or (World Trade Organization Agreement). has shown the government's seriousness in supporting a free/open economic system, and indirectly spurring companies in Indonesia to further increase their competitiveness. The implementation of Intellectual Property can spur economic growth, including in the MSME sector. Regulations for MSME Empowerment have been regulated in Government Regulation Number 7 of 2021 concerning facilitation, protection, and empowerment of cooperatives for micro, small and medium enterprises MSME actors must understand MSME protection regarding intellectual property rights, because they can avoid losses when their intellectual property is recognized by perpetrators. another economy. The government will always try to support the development of small and medium enterprises in Indonesia. This study aims to determine the Implementation of Intellectual Property Rights in MSME Actors in Semarang Regency and the Obstacles that occur in the Implementation of Intellectual Property Rights in MSME. This study uses a juridical-empirical approach using interview data with UMPRI staff at the Office of Cooperatives, Micro Enterprises, Industry and Trade and the Head of UKM Semarang Regency, observation of implementation at the Office of Cooperatives, Micro Enterprises, Industry and Trade as the main data that is relevant to the office at Office of Cooperatives, Micro Enterprises, Industry and Trade in Candirejo, West Ungaran District. The results of the final analysis concluded that: Intellectual Property Rights in Semarang Regency have an activity program to facilitate the ease of licensing for MSMEs, namely the implementation of socialization and or registration on Brand Rights. One of the factors hindering the growth of Micro, Small and Medium Enterprises in Semarang Regency is their obstacles in Capital, Human Resources and Market Segments. Abstrak Kekayaan Intelektual sebagaimana di definisikan dalam Undang-Undang Nomor 7 Tahun 1994 tentang pengesahan WTO atau (World Trade Organization Agreement). telah menunjukan keseriusan Pemerintah dalam mendukung sistem perekonomian yang bebas/terbuka, dan secara tidak langsung memacu perusahaan di Indonesia untuk lebih meningkatkan daya saingnya. Pelaksanaan Kekayaan Intelektual dapat memacu pertumbuhan perekonomian, termasuk pada sektor UMKM. Peraturan terhadap Pemberdayaan UMKM telah di atur dalam Peraturan Pemerintah Nomor 7 tahun 2021 tentang kemudahan, perlindungan, dan pemberdayaan koperasi usaha mikro kecil dan menengah Pelaku UMKM harus memahami perlindungan UMKM tentan hak kekayaan intelektual, karena mereka dapat terhindar dari kerugian ketika kekayaan intelektualnya diakui oleh pelaku ekonomi lain. Pemerintah akan selalu berusaha untuk mendukung pengembangan usaha kecil dan menengah di Indonesia. Penelitian ini bertujuan untuk mengetahui Pelaksanaan Hak Kekayaan Intelektual pada Pelaku UMKM di Kabupaten Semarang dan Hambatan yang terjadi atas Pelaksanaan Hak Kekayaan Intelektual pada UMKM. Penelitian ini menggunakan metode pendekatan yuridis-empiris dengan menggunakan data wawancara kepada Staff umpri Dinas Koperasi, Usaha Mikro, Perindustrian dan Perdagangan dan Ketua UMKM Kabupaten Semarang, observasi pelaksanaan di Dinas Koperasi, Usaha Mikro, Perindustrian dan Perdagangan sebagai data utama yang beraloksikan di kantor di Dinas Koperasi, Usaha Mikro, Perindustrian dan Perdagangan di Candirejo, Kecamatan Ungaran Barat. Hasil analisis akhir diperoleh kesimpulan bahwa: Hak Kekayaan Intelektual di Kabupaten Semarang terdapat program kegiatan memfasilitasi kemudahan perizinan bagi UMKM yaitu pelaksanaan sosialisasi dan atau pendaftaran di Hak Merek. Faktor yang menghambat Pertumbuhan Usaha Mikro Kecil Menengah di Kabupaten Semarang salah satunya hambatan mereka di Modal, Sumber Daya Manusia dan Segmen Pasar.